1H NMR-based metabolomics reveals bioactive compounds from the diatom Halamphora sp. extracted with different solvents - Abd-Ghafar, Siti Zulaikha; Zolkeflee, Nur Khaleeda Zulaikha; Baharuddin, Ninie; Rudiyanto, R.; M, Maulidiani; Ikhsan, Natrah; Abas, Faridah (Taylor and Francis, 2026)
The effect of different solvent extractions on the metabolome of the diatom Halamphora sp. and their correlation with 2,2-diphenyl-1-picrylhydrazyl (DPPH) and nitric oxide (NO) free radical scavenging activities were investigated using proton nuclear magnetic resonance (1H NMR)-based metabolomics. Evaluation of the DPPH and NO scavenging activities of Halamphora sp. extracted with methanol, ethanol, acetone, chloroform or hexane revealed that the acetone and chloroform extracts exhibited the highest activities, with DPPH scavenging of 44.7% and NO scavenging of 107.5%, respectively. In total, 30 metabolites were putatively identified including amino acids, fatty acids, sugars, phenolics, carotenoids and pigments. According to the partial least square model, metabolites contributing to the observed bioactivities included valine, alanine, leucine, linoleic acid, palmitic acid, sucrose, glucose, astaxanthin, canthaxanthin, lutein, zeaxanthin, violaxanthin, fucoxanthin, fucoxanthinol, choline and cholesterol. These findings demonstrate that the acetone and chloroform extracts of Halamphora sp. can serve as source of bioactive metabolites with antioxidant potential. Moreover, the present 1H NMR metabolomics approach proved to be a valuable tool for metabolites identification in microalgae, further supporting the potential of Halamphora sp. as a sustainable and nutritionally rich source for aquafeed applications.